Strengthening Banking Literacy to Optimize Small and Medium Enterprises (SMEs) Business Transactions in Subang Regency - Muharam, Hari; Gursida, Hari; Salmah; Apriyani, Karina; Sutarto, Bambang; Rukmana, Dwita; Suryaman, Maman (International Journal of Research in Community Services, 2025)
Small micro and medium enterprises (SMEs) in Subang Regency are still not optimal in using digital financial products in their business transactions. This is due to their limited understanding of digital financial products and how to access them. Basedon these conditions, this community service program is aimed at increasing the literacy of digital financial products owned by banks for SMEs under the guidance of UPTD-PLUT KUMKM Subang Regency. Activities begin with providing training, monitoring and evaluation. The training provided focused on knowledge and understanding of the importance of using digital finance in SMEs business management as well as the introduction of bank digital financial products such as internet banking, mobile banking, and QRIS. In addition, participants also gained an understanding of financing, especially the working capital financing credit to individuals on the SMEs scale who are productive and viable but do not yet have additional collateral or the additional collateral is not sufficient that called Kredit Usaha Rakyat (KUR), which includes procedures, requirements, loan value, term, and installment simulations. The methods used involved lectures and interactive discussions, while the effectiveness of the training was evaluated through pre-test and post-test to assess the participants' knowledge improvement. The results showed that the training was effective in improving participants' understanding. Based on spiderweb analysis, there was a significant increase in several banking literacy indicators. Participants also showed high enthusiasm during the discussion sessions and better understood the use of digital financial products to support business financial management. Overall, this program succeeded in strengthening the banking literacy of SMEs in Subang Regency, especially in knowing and utilizing digital banking services and financing such as KUR. This increased understanding is expected to help SMEs optimize their business management through digitalization to support better business growth.